Answer:
The Taylor series for
, the first three non-zero terms are
and the interval of convergence is ![( -\infty, \infty )](https://tex.z-dn.net/?f=%28%20-%5Cinfty%2C%20%5Cinfty%20%29)
Step-by-step explanation:
<u>These are the steps to find the Taylor series for the function</u> ![sin^2(3 x)](https://tex.z-dn.net/?f=sin%5E2%283%20x%29)
- Use the trigonometric identity:
![sin^{2}(x)=\frac{1}{2}*(1-cos(2x))\\ sin^{2}(3x)=\frac{1}{2}*(1-cos(2(3x)))\\ sin^{2}(3x)=\frac{1}{2}*(1-cos(6x))](https://tex.z-dn.net/?f=sin%5E%7B2%7D%28x%29%3D%5Cfrac%7B1%7D%7B2%7D%2A%281-cos%282x%29%29%5C%5C%20sin%5E%7B2%7D%283x%29%3D%5Cfrac%7B1%7D%7B2%7D%2A%281-cos%282%283x%29%29%29%5C%5C%20sin%5E%7B2%7D%283x%29%3D%5Cfrac%7B1%7D%7B2%7D%2A%281-cos%286x%29%29)
2. The Taylor series of ![cos(x)](https://tex.z-dn.net/?f=cos%28x%29)
Substituting y=6x we have:
3. Find the Taylor series for ![sin^2(3x)](https://tex.z-dn.net/?f=sin%5E2%283x%29)
(1)
(2)
Substituting (2) in (1) we have:
![\frac{1}{2} (1-\sum_{n=0}^{\infty}\frac{-1^{n}6^{2n}x^{2n}}{(2n)!})\\ \frac{1}{2}-\frac{1}{2} \sum_{n=0}^{\infty}\frac{-1^{n}6^{2n}x^{2n}}{(2n)!}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%20%281-%5Csum_%7Bn%3D0%7D%5E%7B%5Cinfty%7D%5Cfrac%7B-1%5E%7Bn%7D6%5E%7B2n%7Dx%5E%7B2n%7D%7D%7B%282n%29%21%7D%29%5C%5C%20%5Cfrac%7B1%7D%7B2%7D-%5Cfrac%7B1%7D%7B2%7D%20%5Csum_%7Bn%3D0%7D%5E%7B%5Cinfty%7D%5Cfrac%7B-1%5E%7Bn%7D6%5E%7B2n%7Dx%5E%7B2n%7D%7D%7B%282n%29%21%7D)
Bring the factor
inside the sum
![\frac{6^{2n}}{2}=9^{n}2^{2n-1} \\ (-1^{n})(9^{n})=(-9^{n} )](https://tex.z-dn.net/?f=%5Cfrac%7B6%5E%7B2n%7D%7D%7B2%7D%3D9%5E%7Bn%7D2%5E%7B2n-1%7D%20%5C%5C%20%28-1%5E%7Bn%7D%29%289%5E%7Bn%7D%29%3D%28-9%5E%7Bn%7D%20%29)
![\frac{1}{2}-\sum_{n=0}^{\infty}\frac{-9^{n}2^{2n-1}x^{2n}}{(2n)!}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D-%5Csum_%7Bn%3D0%7D%5E%7B%5Cinfty%7D%5Cfrac%7B-9%5E%7Bn%7D2%5E%7B2n-1%7Dx%5E%7B2n%7D%7D%7B%282n%29%21%7D)
Extract the term for n=0 from the sum:
![\frac{1}{2}-\sum_{n=0}^{0}\frac{-9^{0}2^{2*0-1}x^{2*0}}{(2*0)!}-\sum_{n=1}^{\infty}\frac{-9^{n}2^{2n-1}x^{2n}}{(2n)!}\\ \frac{1}{2} -\frac{1}{2} -\sum_{n=1}^{\infty}\frac{-9^{n}2^{2n-1}x^{2n}}{(2n)!}\\ 0-\sum_{n=1}^{\infty}\frac{-9^{n}2^{2n-1}x^{2n}}{(2n)!}\\ sin^{2}(3x)=-\sum_{n=1}^{\infty}\frac{-9^{n}2^{2n-1}x^{2n}}{(2n)!}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D-%5Csum_%7Bn%3D0%7D%5E%7B0%7D%5Cfrac%7B-9%5E%7B0%7D2%5E%7B2%2A0-1%7Dx%5E%7B2%2A0%7D%7D%7B%282%2A0%29%21%7D-%5Csum_%7Bn%3D1%7D%5E%7B%5Cinfty%7D%5Cfrac%7B-9%5E%7Bn%7D2%5E%7B2n-1%7Dx%5E%7B2n%7D%7D%7B%282n%29%21%7D%5C%5C%20%5Cfrac%7B1%7D%7B2%7D%20-%5Cfrac%7B1%7D%7B2%7D%20-%5Csum_%7Bn%3D1%7D%5E%7B%5Cinfty%7D%5Cfrac%7B-9%5E%7Bn%7D2%5E%7B2n-1%7Dx%5E%7B2n%7D%7D%7B%282n%29%21%7D%5C%5C%200-%5Csum_%7Bn%3D1%7D%5E%7B%5Cinfty%7D%5Cfrac%7B-9%5E%7Bn%7D2%5E%7B2n-1%7Dx%5E%7B2n%7D%7D%7B%282n%29%21%7D%5C%5C%20sin%5E%7B2%7D%283x%29%3D-%5Csum_%7Bn%3D1%7D%5E%7B%5Cinfty%7D%5Cfrac%7B-9%5E%7Bn%7D2%5E%7B2n-1%7Dx%5E%7B2n%7D%7D%7B%282n%29%21%7D)
<u>To find the first three non-zero terms you need to replace n=3 into the sum</u>
![sin^{2}(3x)=\sum_{n=1}^{\infty}\frac{-9^{n}2^{2n-1}x^{2n}}{(2n)!}\\ \sum_{n=1}^{3}\frac{-9^{3}2^{2*3-1}x^{2*3}}{(2*3)!} = 9x^{2} -27x^{4}+\frac{162}{5}x^{6}](https://tex.z-dn.net/?f=sin%5E%7B2%7D%283x%29%3D%5Csum_%7Bn%3D1%7D%5E%7B%5Cinfty%7D%5Cfrac%7B-9%5E%7Bn%7D2%5E%7B2n-1%7Dx%5E%7B2n%7D%7D%7B%282n%29%21%7D%5C%5C%20%5Csum_%7Bn%3D1%7D%5E%7B3%7D%5Cfrac%7B-9%5E%7B3%7D2%5E%7B2%2A3-1%7Dx%5E%7B2%2A3%7D%7D%7B%282%2A3%29%21%7D%20%3D%209x%5E%7B2%7D%20-27x%5E%7B4%7D%2B%5Cfrac%7B162%7D%7B5%7Dx%5E%7B6%7D)
<u>To find the interval on which the series converges you need to use the Ratio Test that says</u>
For the power series centered at x=a
![P(x)=C_{0}+C_{1}(x-a)+C_{2}(x-a)^{2}+...+ C_{n}(x-a)^{n}+...,](https://tex.z-dn.net/?f=P%28x%29%3DC_%7B0%7D%2BC_%7B1%7D%28x-a%29%2BC_%7B2%7D%28x-a%29%5E%7B2%7D%2B...%2B%20C_%7Bn%7D%28x-a%29%5E%7Bn%7D%2B...%2C)
suppose that
. Then
- If
the the series converges for all x - If
then the series converges for all ![|x-a|](https://tex.z-dn.net/?f=%7Cx-a%7C%3CR)
- If R=0, the the series converges only for x=a
So we need to evaluate this limit:
![\lim_{n \to \infty} |\frac{\frac{-9^{n}2^{2n-1}x^{2n}}{(2n)!}}{\frac{-9^{n+1}2^{2*(n+1)-1}x^{2*(n+1)}}{(2*(2n+1))!}} |](https://tex.z-dn.net/?f=%5Clim_%7Bn%20%5Cto%20%5Cinfty%7D%20%7C%5Cfrac%7B%5Cfrac%7B-9%5E%7Bn%7D2%5E%7B2n-1%7Dx%5E%7B2n%7D%7D%7B%282n%29%21%7D%7D%7B%5Cfrac%7B-9%5E%7Bn%2B1%7D2%5E%7B2%2A%28n%2B1%29-1%7Dx%5E%7B2%2A%28n%2B1%29%7D%7D%7B%282%2A%282n%2B1%29%29%21%7D%7D%20%7C)
Simplifying we have:
![\lim_{n \to \infty} |-\frac{(n+1)(2n+1)}{18x^{2} } |](https://tex.z-dn.net/?f=%5Clim_%7Bn%20%5Cto%20%5Cinfty%7D%20%7C-%5Cfrac%7B%28n%2B1%29%282n%2B1%29%7D%7B18x%5E%7B2%7D%20%7D%20%7C)
Next we need to evaluate the limit
![\lim_{n \to \infty} |-\frac{(n+1)(2n+1)}{18x^{2} } |\\ \frac{1}{18x^{2} } \lim_{n \to \infty} |-(n+1)(2n+1)}|}](https://tex.z-dn.net/?f=%5Clim_%7Bn%20%5Cto%20%5Cinfty%7D%20%7C-%5Cfrac%7B%28n%2B1%29%282n%2B1%29%7D%7B18x%5E%7B2%7D%20%7D%20%7C%5C%5C%20%5Cfrac%7B1%7D%7B18x%5E%7B2%7D%20%7D%20%5Clim_%7Bn%20%5Cto%20%5Cinfty%7D%20%7C-%28n%2B1%29%282n%2B1%29%7D%7C%7D)
-(n+1)(2n+1) is negative when n -> ∞. Therefore ![|-(n+1)(2n+1)}|=2n^{2}+3n+1](https://tex.z-dn.net/?f=%7C-%28n%2B1%29%282n%2B1%29%7D%7C%3D2n%5E%7B2%7D%2B3n%2B1)
You can use this infinity property
when a>0 and n is even. So
![\lim_{n \to \infty} |-\frac{(n+1)(2n+1)}{18x^{2} } | \\ \frac{1}{18x^{2}} \lim_{n \to \infty} 2n^{2}+3n+1=\infty](https://tex.z-dn.net/?f=%5Clim_%7Bn%20%5Cto%20%5Cinfty%7D%20%7C-%5Cfrac%7B%28n%2B1%29%282n%2B1%29%7D%7B18x%5E%7B2%7D%20%7D%20%7C%20%5C%5C%20%5Cfrac%7B1%7D%7B18x%5E%7B2%7D%7D%20%5Clim_%7Bn%20%5Cto%20%5Cinfty%7D%202n%5E%7B2%7D%2B3n%2B1%3D%5Cinfty%20)
Because this limit is ∞ the radius of converge is ∞ and the interval of converge is
.